Use of video SOP at the pharmaceutical quality system management as alternative to reduce deviations ocurrence (Research, Society and Development, 2020)
In the presente article, it was performed the analyse of the obtained results with the implementation of Standard Operating Procedure with video, analternative called vídeo SOP, in a multinational company in the pharmaceutical industry. The company had a history of records of quality deviations related to procedures and training, such as lack of adherence by employees, lack of detailed instructions for operations, etc. After realizing that some implemented corrective actions were not effective in reducing the number of deviations, the proposed solution was to use explanatory videos as part of the standard operating procedure. With the adopted measure, it was expected that the audio visual resource would facilitate to fix the SOPs content during training, improving the adherence of employees in practice. The general objective of the article was to evaluate data on quality deviations of the company one year after the implementation of the vídeo SOP to check if there were improvements and if the action can be considered effective. The comparison between the number of deviations before and after the adopted measure demonstrates that the use of vídeo SOP has brought benefits to the company.